2016
DOI: 10.3892/mmr.2016.5659
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of TACC3 inhibits trophoblast cell migration and invasion through the PI3K/Akt signaling pathway

Abstract: The insufficient invasion of trophoblasts is known to be correlated with the development of preeclampsia. Transforming acidic coiled‑coil protein 3 (TACC3), a member of the TACC domain family, is important in the regulation of cell differentiation, migration and invasion. However, the role of TACC3 in trophoblast function during placental development remains to be fully elucidated. The present study aimed to determine the expression and function of TACC3 in human placenta and to examine the underlying mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 31 publications
3
16
0
Order By: Relevance
“…4A). Furthermore, MMP-2 and MMP-9 have been shown to be critical in trophoblast invasion by degrading the extracellular matrix (30). Our results showed that ANXA4 overexpression significantly increased the protein expression of MMP-2 and MMP-9 in HTR-8/SVneo cells (Fig.…”
Section: Decreased Anxa4 Pi3k P-akt and P-enos Expression In Pe Plsupporting
confidence: 53%
See 2 more Smart Citations
“…4A). Furthermore, MMP-2 and MMP-9 have been shown to be critical in trophoblast invasion by degrading the extracellular matrix (30). Our results showed that ANXA4 overexpression significantly increased the protein expression of MMP-2 and MMP-9 in HTR-8/SVneo cells (Fig.…”
Section: Decreased Anxa4 Pi3k P-akt and P-enos Expression In Pe Plsupporting
confidence: 53%
“…The PI3K/Akt signaling pathway plays a critical role in mediating the growth-factor-dependent regulation of trophoblast growth and invasion. A previous study has stated that migration and invasion of trophoblast cells are suppressed through inhibition of the PI3K/Akt pathway (30). PI3K and Akt are involved in regulating trophoblast invasion through the upregulation of MMP-9 and tissue inhibitor of metalloproteinase-1 (TIMP-1) expression by epidermal growth factor (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TACC3 is highly expressed in most cancers tissues, such as prostate cancer (Li et al, ), glioma (Sun et al, ), cholangiocarcinoma (He et al, ), and colorectal cancer (Du et al, ), lung cancer (Jiang et al, ), gastric cancer (Yun et al, ). However, the expression of TACC3 is down‐regulated in thyroid cancer and ovarian carcinoma and preeclampsia (Peters et al, ; Ulisse et al, ; Zhu, Cao, Li, & Wang, ). Extensive and abnormal expression patterns of TACC3 in cancers make it more attractive than the other two proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Among members of the MMP family, MMP-2 and MMP-9 are the most studied and play the most important roles in trophoblast cell invasion [3941]. Its inhibitory factor, TIMPs, inhibits invasion [42,43]. To test our hypothesis, we studied the impact of si-BRIT1 on the activities of MMP-2, MMP-9, TIMP-1, and TIMP-2 in TC.…”
Section: Discussionmentioning
confidence: 99%